Co-infection between Entamoeba histolytica and Helicobacter Pylori in Patients at Wasit Province - Abdulsada A. Rahi; Magda A. Ali; Sima’a H. Mohammed (Indian Journal of Forensic Medicine & Toxicology, 2021)
The current study was conducted at Wasit province, Iraq during the period from 28 October 2020 to28 December 2020. The study included one hundred stool samples taken from questionable patients ofEntamoeba histolytica and Helicobacter pylori. Samples were collected from patient attended to GeneralHospital of Martyr Fairuz at Hay district , Saeed Health center and Hospital of Al-Kut. All samples havebeen checked using direct smear lugol’s iodine stain for Entamoeba histolytica and dipstick for Helicobacterpylori. The result showed that 40 samples (40%) out of 100 patients were gave positive by rapid test cassette;females 23 (23%) positive samples and males 17(17%). While 14 samples (14%)out of 100 samples werepositive for Entamoeba histolytica. The highest infection in females 8(8%) and the lowest in males 6(6%).The result showed 10 samples (10%) out of 100 patients positive for both E. histolytica and H. pylori. Thehighest infection was recorded in females 6(6%) and the lowest in males 4(4%).The highest infection of H.pylori in age group (39 and more) years ; females recorded 6(6%) and malesrecorded 6(6%), while the lowest infection in group (>1) years old ; females recorded 1(1%) and malesrecorded 1(1%). The infection rate of Entamoeba histolytica was highest in age group (1-13) years old ;females was recorded 1(1%) and males was recorded 4(4%) , while the lowest in age group (26-39) years old; females recorded 1(1%) while males without infection. Infection with both E.histolytica and H.pylori wasrecorded the highest in group (39 and more) years old ; females was recorded 3(3%) and males was recorded2(2%) while the group (>1) years old do not recorded infections.